Transformasi Kelokalan melalui Tanda Visual & Verbal pada Desain - Hartanti, Monica (Zenit, 2013)
Food is one of the human cultures that is constantly evolving and transforming both the physic and idea. Existence of traditional  instant spices that are packed with attractive visualization design; impressed traditionally, practical and safe were able to convince consumers to use. That phenomenon creates transformation of  locality to industrial locality that will gradually erode the value of originality traditions that exist in traditional foods.Keywords: traditional foods, transformation, locality, packaging design